2010
DOI: 10.1371/journal.pntd.0000811
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Country Evaluation of the Sensitivity and Specificity of Two Commercially-Available NS1 ELISA Assays for Dengue Diagnosis

Abstract: BackgroundEarly diagnosis of dengue can assist patient triage and management and prevent unnecessary treatments and interventions. Commercially available assays that detect the dengue virus protein NS1 in the plasma/serum of patients offers the possibility of early and rapid diagnosis.Methodology/Principal FindingsThe sensitivity and specificity of the Pan-E Dengue Early ELISA and the Platelia™ Dengue NS1 Ag assays were compared against a reference diagnosis in 1385 patients in 6 countries in Asia and the Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
131
2
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(152 citation statements)
references
References 27 publications
(34 reference statements)
14
131
2
5
Order By: Relevance
“…However, an early and precise dengue diagnostic is important for patient management, to avoid dengue severity and mortality and, ultimately, to control epidemics. 8,21,26 Our results agree with others who reported that the combination of two or more diagnostic strategies is needed to improve the diagnostic accuracy of DENV infection. 8,[21][22][23]26 Combining direct DENV detection and antibody-based tests seems to be a particularly promising strategy.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, an early and precise dengue diagnostic is important for patient management, to avoid dengue severity and mortality and, ultimately, to control epidemics. 8,21,26 Our results agree with others who reported that the combination of two or more diagnostic strategies is needed to improve the diagnostic accuracy of DENV infection. 8,[21][22][23]26 Combining direct DENV detection and antibody-based tests seems to be a particularly promising strategy.…”
Section: Discussionsupporting
confidence: 91%
“…21,23 Guzman and others 8 also reported lower sensitivity of NS1 antigen detection in American countries (Nicaragua and Venezuela) compared with Asian countries. 8,24 The occurrence of secondary infections also seems to have an impact on the accuracy of IgM detection. Indeed, higher sensitivity of the anti-IgM SD Bioline Dengue Duo was evidenced in primary DENV infections compared with secondary infections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The monoclonal antibody used in the test has been shown to detect the NS1 protein of all 4 DENV serotypes, albeit with some differences in sensitivity. 37 Moreover, Tan and others 28 showed that all 4 DENV serotypes could be readily detected in infected mosquitoes using the Dengue NS1 Ag Strip test from the same manufacturer as the Platelia Dengue NS1 kit. Nonetheless, it would be prudent to determine the ability to detect DENV-1, -3, and -4 NS1 in mosquitoes subjected to the simulated field collection conditions by use of the Platelia Dengue NS1 Ag kit.…”
Section: Discussionmentioning
confidence: 99%